METHODOLOGICAL BASES OF FORMATION OF INFORMATION AND COMMUNICATION COMPETENCE OF FUTURE TEACHERS - Baktybayev, Ж.Ш; Turysbekova, М.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article determines the effectiveness of increasing the volume of knowledge, skills and abilities of students in the context of informatization in such regulatory documents as the State Program for the Development of Education of the Republic of Kazakhstan for 2020-2025, the Law of the Republic of Kazakhstan "On Education", the State Program "Digital Kazakhstan", theoretical basics of literacy of information and communication competence of a teacher. The article discusses the need for any future teacher in the information society to master the basics of information knowledge, use information and communication technologies (ICT) for self-education and develop skills to use their potential as a cognitive and didactic tool in professional activity. The needs of future teachers in the country's universities and the main directions of social and pedagogical activities are described. There are also links to the formation of information and communication competencies of future teachers and a review of the work of domestic and foreign scientists.